Fekete-Szego inequalities for certain subclass of analytic bi-univalent functions associated with chebyshev polynomials / Nurul Shahira Izzaty Sabran, Nur Shafiqah Zulkifle and Nurul Amanina Abdul Husin - Sabran, Nurul Shahira Izzaty; Nur Shafiqah, Zulkifle; Abdul Husin, Nurul Amanina (2018)
Geometric function theory involves in studying the properties of analytic and bi-univalent functions. In the area of geometric function theory. a new subclass of function is constantly introduced and it is in nature for researchers to find its properties. Through Chebyshev polynomial, a new class of function is defined and two of its properties are to be studied.